2016
DOI: 10.1002/hed.24366
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise therapy for trismus secondary to head and neck cancer: A systematic review

Abstract: Changes in mouth opening ranged considerably and no stretching technique was superior to others regarding either prevention or treatment of trismus. Clinical guidelines cannot be given based on this systematic review. © 2016 Wiley Periodicals, Inc. Head Neck 39: 160-169, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 41 publications
1
50
0
2
Order By: Relevance
“…Recently, a systematic review by Kamstra et al [171] identified 12 studies, ranging from chart reviews to randomized controlled trials that analyzed the effect of therapeutic measures on mouth opening after trismus occurred. The duration of the therapy in these studies ranged from 1 to 9 months, the number of exercise sessions per day varied from 2 to 10, with 3 to 8 repetitions, and the duration of stretch ranged from 6 seconds to 60 minutes.…”
Section: Trismusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic review by Kamstra et al [171] identified 12 studies, ranging from chart reviews to randomized controlled trials that analyzed the effect of therapeutic measures on mouth opening after trismus occurred. The duration of the therapy in these studies ranged from 1 to 9 months, the number of exercise sessions per day varied from 2 to 10, with 3 to 8 repetitions, and the duration of stretch ranged from 6 seconds to 60 minutes.…”
Section: Trismusmentioning
confidence: 99%
“…An increase in mouth opening was reported in the majority of studies, although, in many, the final mean mouth opening was still <35 mm suggesting that even after therapy, a proportion of patients still suffer from trismus. No exercise technique was found to be superior to others, and the results were influenced by compliance with the exercises and the time interval between oncologic treatment and the start of the exercises (the sooner, the better) [171]. A recently reported study using the Dynasplint Trismus System confirmed that early detection of trismus and the early start of exercise therapy ensure a better outcome of mouth opening [172].…”
Section: Trismusmentioning
confidence: 99%
“…In order to prevent or to treat trismus, stretching regimens are often prescribed to increase mouth opening 9 . In 2016, a systematic review analyzed the effects of various stretching regimens, but none of them was found to be superior 10 . It has been suggested that early initiation of a therapy for trismus results in a greater improvement in mouth opening 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several interventions for this impairment have been described in the literature: application of botulinum toxin, use of medicines, surgical procedures, and direct therapy with the use of commercial devices or through programs with orofacial myofunctional exercises (7)(8)(9)(10)(11)(12)(13)(14) . In addition to possible difficulties associated with cost and access, cancer patients may present limitations to certain types of intervention because of the characteristics of disease evolution and the effects of cancer treatment (2,5,8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Surgeries aiming to obtain greater mouth opening are more indicated in cases resistant to therapy (9) . The use of commercial devices has proven to be effective (11) , but because of their high cost and, especially, of the evidence of increased mouth opening with conventional exercise programs (10,12) , they would not be suitable for all patients (14) . Muscle exercise programs have not yet proven to be effective as a preventive measure (13) .…”
Section: Introductionmentioning
confidence: 99%